Challenges and coping mechanisms of nurse involved in the resuscitation of patients in an emergency unit at selected public hospitals in Mopani District, Limpopo Province - Makgoba, Mmaseshoka Charmaine (My University, 2022)
Background Resuscitation of patients in an emergency unit has been one of the greatest challenges for nurses. Many deaths in hospitals happen within 24 hours of admission. Some of these deaths could be prohibited if the patients were effectively identified quickly and treatment commenced without delay. Emergency care has always been a weak and under-emphasised component of African healthcare systems. Purpose To determine the challenges and coping mechanisms of nurses involved in the resuscitation of patients in an emergency unit at selected public hospitals in Mopani District, Limpopo Province. Research Method A qualitative explorative, descriptive and contextual research design was used to conduct this study. Data was collected using a one-to-one semi-structured interview with an interview guide. The interviews were audiotaped and field notes were taken to capture the non-verbal cues. Data was collected from professional nurses working in the emergency unit sampled through a purposive sampling method. Data collection was conducted until data saturation was achieved with eighteen participants. Data were transcribed verbatim and analysed using Tech’s open coding method with the assistance of an independent coder. Measures to ensure trustworthiness, credibility, conformability, transferability and dependability were all ensured. Ethical considerations, ethical clearance, permission, informed consent, privacy, confidentiality, anonymity, beneficence, non-maleficence and the principle of justice were adhered to throughout the study. Results The findings of the study revealed the perceptions of nurses' toward the resuscitation process with challenges experienced by nurses during resuscitation in the emergency unit. Nurses also reported the effect such as inadequate medical equipment, inadequate pharmaceutical supplies, inadequate infrastructure, v inadequate multi-disciplinary support services, inadequate support services (transport, EMS, cleaning, security services), and inadequate managerial and organisational support effects of challenges on their work during resuscitation in the emergency unit and verbalised their developed coping mechanisms with resuscitation in the emergency unit. The nurses also indicated their suggested coping mechanisms, which they contemplate could assist them during the resuscitation of patients in the emergency unit to minimise the traumatic experiences following unsuccessful resuscitation. Recommendations The study, therefore, recommended that supporting, debriefing sessions, group therapy and counselling should be provided by the hospital to the psychologically affected nurses. The hospital management has to motivate the provision of an adequate number of nurses and material resources in the emergency units to maintain acceptable emergency care. A sufficient number of nurses should be awarded study leave to register for post-basic training on advanced trauma to increase capacity in the emergency unit.
Thesis (M. Nursing) -- University of Limpopo, 2023
Keywords: Challenge; Nurse; Resuscitation; Emergency unit; Coping mechnism; Adjustment (Psychology); Coping response inventory; Emergency nursing; Resuscitation; Nursing -- Psychological aspects